Effects of maximal power and the force-velocity profile on sprint acceleration performance according to maturity status and sex - Sudlow, A.; Galantine, P.; Sordo, G. D.; Raymond, J.-J.; Dalleau, G.; Peyrot, N.; Duché, P. (Journal of Sports Sciences, 2025)
This study aimed to determine whether maturational and sex-related differences in sprint times were accompanied by changes in relative maximal power (Pmax), force-velocity profiles (SFV) and optimal sprint distances (xopt). Sprint times and continuous velocity-time data were collected using a radar. Inverse dynamics applied to the centre of mass provided accurate estimations of force-velocity relationship parameters (Pmax, F0, v0, SFV, xopt) and technical variables (RFmax, DRF). Somatic maturity was determined from peak height velocity (PHV). Performance increased with maturation in girls and boys (p < 0.001, d = 0.86-2.78) accompanied by increases in relative Pmax from pre to post-PHV (p < 0.011-0.001, d = 0.98-5.20). Increases in relative Pmax were predominantly due to more velocity-oriented profiles (p < 0.007-0.001, d = 0.76-1.41). xopt, RFmax and DRF also increased with maturation (p < 0.030-0.001, d = 0.87-3.40). Pmax increases in girls and boys throughout maturation enabling them to reduce sprint times. Both girls and boys increased Pmax through a shift to more velocity-oriented profiles. However, plateaus in F0 and RFmax were present from pre-PHV in girls, while boys had slower development from mid-PHV. Improving Pmax through increases in F0 and RFmax, while maintaining a velocity-oriented profile, will likely benefit youth sprint performance. A specific focus on these parameters is necessary from pre-PHV onwards in girls and from mid-PHV in boys.